Role of social capital in improving the quality of life and social justice in Mashhad, Iran. (October 2017) - Rastegar, Mohsen; Hatami, Hossein; Mirjafari, Raziehsadat
Abstract: One of the main objectives of the development is the improvement of life quality. In Developing countries, lack of urban management planners' attention to social aspects and human resources caused many problems for improving citizens' quality of life and their environment. In this regard, social capital is closely related to the quality of life. Considering the unique features of Mashhad metropolis in terms of pilgrimage and tourism, the city with a population over 3 million faces a higher degree of rapid population growth. This metropolis has been encountering problems such as poverty, low employment rates, lack of unity and social cohesion, gender inequality and low quality of life indicator for many years. Therefore, solving or at least mitigating these problems is not possible without paying attention to attitudes and social capital. In this study, the data required have been obtained by the questionnaire of 380 civilians and 36 members of municipal managers. The results of the present study showed that institutions governing the city, especially municipality and city council, do not care about the opinions and views of people in planning, and thus public participation is very low. Therefore, there is a difference between the views of managers and citizens about the role of social capital in improving the quality of life.